Changes in the gastric enteric nervous system and muscle: A case report on two patients with diabetic gastroparesis - Lurken Matthew S; Vittal Harsha; Gomez Guillermo; Pehlivanov Nonko D; Pasricha Pankaj J; Farrugia Gianrico (BMC Gastroenterology, 2008)
Abstract Background The pathophysiological basis of diabetic gastroparesis is poorly understood, in large part due to the almost complete lack of data on neuropathological and molecular changes in the stomachs of patients. Experimental models indicate various lesions affecting the vagus, muscle, enteric neurons, interstitial cells of Cajal (ICC) or other cellular components. The aim of this study was to use modern analytical methods to determine morphological and molecular changes in the gastric wall in patients with diabetic gastroparesis. Methods Full thickness gastric biopsies were obtained laparoscopically from two gastroparetic patients undergoing surgical intervention and from disease-free areas of control subjects undergoing other forms of gastric surgery. Samples were processed for histological and immunohistochemical examination. Results Although both patients had severe refractory symptoms with malnutrition, requiring the placement of a gastric stimulator, one of them had no significant abnormalities as compared with controls. This patient had an abrupt onset of symptoms with a relatively short duration of diabetes that was well controlled. By contrast, the other patient had long standing brittle and poorly controlled diabetes with numerous episodes of diabetic ketoacidosis and frequent hypoglycemic episodes. Histological examination in this patient revealed increased fibrosis in the muscle layers as well as significantly fewer nerve fibers and myenteric neurons as assessed by PGP9.5 staining. Further, significant reduction was seen in staining for neuronal nitric oxide synthase, heme oxygenase-2, tyrosine hydroxylase as well as for c-KIT. Conclusion We conclude that poor metabolic control is associated with significant pathological changes in the gastric wall that affect all major components including muscle, neurons and ICC. Severe symptoms can occur in the absence of these changes, however and may reflect vagal, central or hormonal influences. Gastroparesis is therefore likely to be a heterogeneous disorder. Careful molecular and pathological analysis may allow more precise phenotypic differentiation and shed insight into the underlying mechanisms as well as identify novel therapeutic targets.